2010
DOI: 10.1016/j.molonc.2010.11.002
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation patterns in luminal breast cancers differ from non‐luminal subtypes and can identify relapse risk independent of other clinical variables

Abstract: Subtypes DNA methylation MOMA Survival Epigenetics A B S T R A C TThe diversity of breast cancers reflects variations in underlying biology and affects the clinical implications for patients. Gene expression studies have identified five major subtypese Luminal A, Luminal B, basal-like, ErbB2þ and Normal-Like. We set out to determine the role of DNA methylation in subtypes by performing genome-wide scans of CpG methylation in breast cancer samples with known expression-based subtypes. Unsupervised hierarchical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
116
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(131 citation statements)
references
References 37 publications
10
116
3
Order By: Relevance
“…Recent studies using array-based methylation analysis have confirmed that the molecular subtypes of breast cancer have subtype-specific methylation profiles. [18][19][20][21] Holm et al 19 demonstrated differences in the methylation profiles of luminal A, luminal B, and basal-like breast cancers, with luminal B and basal-like breast cancers being most and least frequently methylated, respectively. In our study, the number of CpG island loci methylated was highest in the luminal-HER2 subtype and lowest in the basal-like subtype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies using array-based methylation analysis have confirmed that the molecular subtypes of breast cancer have subtype-specific methylation profiles. [18][19][20][21] Holm et al 19 demonstrated differences in the methylation profiles of luminal A, luminal B, and basal-like breast cancers, with luminal B and basal-like breast cancers being most and least frequently methylated, respectively. In our study, the number of CpG island loci methylated was highest in the luminal-HER2 subtype and lowest in the basal-like subtype.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Array-based comprehensive DNA methylation profiling has shown that breast cancer molecular subtypes have their own methylation profiles. [18][19][20][21] Moreover, these different methylation profiles were evident throughout the CpG islands of the genome, not limited to functional genes. 20 Kamalakaran et al 20 reported that the methylation patterns of differentially methylated genes in luminal A tumors were similar to those identified in CD24 þ luminal epithelial cells, and those in basal-like tumors resembled those of CD44 þ breast progenitor cells, suggesting that the methylation patterns of the breast cancer subtypes reflect the methylation patterns of their cells of origin.…”
mentioning
confidence: 99%
“…In addition, hypomethylation of repetitive elements is associated with elevated transcription, while that of normally methylated promoter CpG islands can lead to elevated expression of tumor antigens and possible oncogenes (29). So far, a few genome-wide methylation analyses of breast cancer have been performed in different subtypes of cancer such as luminal/non-luminal (30) and ER + /ER - (15), as well as in non-specified cancer tissues (31). Most of the studies focused on specific genes such as homeobox genes (14), polycomb-binding sites (32) tumor suppressors, and oncogenes, resulting in identification of novel epigenetic markers rather than elucidating the epigenetic regulatory network involved in the carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…One of the first genome wide DNA methylation studies in breast cancer developed methylation-specific digital karyotyping (MSDK) to assess epithelial, myoepithelial, and stromal fibroblasts from normal abreast and cancer tissues [71]. Furthermore, genome wide DNA methylation studies in breast cancer identified gene families that were commonly identified as differentially methylated between non-malignant and tumour included transcription factors (FOX, KLF, PRDM, ZBTB, and ZNF) and gene families involved in cell transport of proteins or vesicles(RAB and SLC) or involvement in cell adhesion (CDH and PCDH) [71][72][73][74]. The pathways and gene families do not appear to have a strong link to hormone metabolism or signalling, it is likely that these genes are not drivers of cancer but rather are secondary events that occur as part of the tumourigenic process [75,76].…”
Section: Dna Methylation and Breast Cancermentioning
confidence: 99%
“…Genome wide DNA methylation studies have supported correlation between DNA methylation and gene expression, particularly the association between CpG islands DNA hypermethylation and gene repression [49,74,77,78]. Using familial breast cancers and BRCA1/2-mutated tumours combined DNA methylation profiles that alone predicted BRCA status, with gene expression and copy number variation (CNV) and found that genes with reduced expression were more likely to be in genomic regions with loss of heterozygosity and/or high levels of DNA methylation.…”
Section: Dna Methylation and Breast Cancermentioning
confidence: 99%